2018
DOI: 10.3389/fendo.2018.00568
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stress, Cortisol Levels, and Maintenance of Vaginal Health

Abstract: Stress stimuli are ubiquitous and women do not enjoy any exemptions. The physiologic “fight-or-flight” response may be deleterious to the female lower genital tract microbiome if the stress stimuli persist for longer than necessary. Persistent exposure to psychosocial stress and stimulation of the hypothalamic-pituitary-adrenal (HPA) and sympathetic-adrenal-medullary (SAM) axes, and associated hormones are risk factors for several infections including genitourinary tract infections. Though this could be due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 135 publications
(178 reference statements)
1
38
0
4
Order By: Relevance
“…These challenges can be lifetime events, emotions, and relations that unfavorably affect the individual's comfort or generate perceived detrimental responses. Very recently, the role of stress over the female lower genital tract has been reviewed [90]. For instance, working with animal models, it has been reported that the persistent exposure to psychosocial stress can lead to an encouragement of the hypothalamic-pituitary-adrenal and sympathetic-adrenal-medullary axes.…”
Section: Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…These challenges can be lifetime events, emotions, and relations that unfavorably affect the individual's comfort or generate perceived detrimental responses. Very recently, the role of stress over the female lower genital tract has been reviewed [90]. For instance, working with animal models, it has been reported that the persistent exposure to psychosocial stress can lead to an encouragement of the hypothalamic-pituitary-adrenal and sympathetic-adrenal-medullary axes.…”
Section: Stressmentioning
confidence: 99%
“…This, in turn, drives a cortisol-induced inhibition of glycogen deposition in vagina, which is translated into an interruption in epithelial maturation that is crucial to keep vaginal homeostasis (included as negative modifiable factor in Figure 1). This phenomenon is especially relevant during pregnancy, where local production of high levels of corticotropin-releasing hormone occurs in the decidua, fetal membranes and placenta [90].…”
Section: Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic use is known to disrupt eubiosis in multiple body niches, but a number of studies in the vagina specifically found that these disruptions do not appear to last (Ding and Schloss, 2014 ; Dunlop et al, 2019 ). A number of studies have identified chronic psychosocial stress as an important mediator of vaginal health (Holtgrave and Crosby, 2003 ; Nansel et al, 2006 ), as mediated by the effect of cortisol on glycogen deposition and mucosal immune function (Amabebe and Anumba, 2018 ). Chronically elevated cortisol levels are known to be immunosuppressive and deplete glycogen stores, potentially impacting the VMB because glycogen-rich epithelium encourages Lactobacillus growth.…”
Section: Determinants Of Vaginal Microbiota Compositionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26] While precise mechanisms remain unknown, it has been postulated that stress influences hormonal pathways leading to changes in host immune response, thereby affecting the cervicovaginal ecosystem. [27][28][29][30] These findings raise questions as to whether stress may promote colonization of the cervicovaginal space with a nonoptimal microbiota in pregnancy.…”
mentioning
confidence: 99%